PENINGKATAN HASIL BELAJAR PENDIDIKAN PANCASILA PADA PESERTA DIDIK KELAS IV SD MELALUI MODEL PJBL - Junita Dwi Fransiska; Nur Aini Insyirotun Nisa; Susilo Tri Widodo; Wulan Aulia Azizah; Muhammad Nurul Udin (LPPM Universitas Cipta Mandiri, 2024)
The purpose of this study was to determine the improvement of Pancasila Education learning outcomes in fourth grade students of Mintobasuki 02 State Elementary School through the PjBL (Project Based Learning) model assisted by concrete media and digital-based media. The research used an experimental method with a descriptive quantitative approach. This type of research is Preexperimental with One-Group Pretest-Posttest design. Subjects were taken from all fourth grade students of Mintobasuki 02 Elementary School totaling 23 students, consisting of 6 boys and 17 girls with simple random sampling technique. Data collection was obtained from interviews, observations, and documentation. The reality that occurs in the field, it is known that during Pancasila Education learning takes place there are some students who pay less attention to the explanation of the teacher because the presentation of material using the lecture method so that it seems monotonous and less interesting. In overcoming these problems, an experiment was conducted to increase students' interest as well as learning outcomes through the PjBL model with the help of concrete media and digital media. The results showed an increase in student learning outcomes, especially in learning Pancasila Education on the material of forms of norms and rules in everyday life. Evidenced by the acquisition of an increase in the average value of the Pretest 57.09 and Post test 76.00. Although when calculated from the N-Gain test the results are less effective because the percentage is less than 75%, there is still a significant increase even though the effect is only about 43.07%. In addition, the development of learning media is also carried out to support the teaching and learning process by utilizing concrete media and digital media so that it can attract students' interest in learning while providing better learning outcomes.